Ants modulate stridulatory signals depending on the behavioural context - A. Masoni (Nature Portfolio, 2021)
Abstract Insect societies require an effective communication system to coordinate members’ activities. Although eusocial species primarily use chemical communication to convey information to conspecifics, there is increasing evidence suggesting that vibroacoustic communication plays a significant role in the behavioural contexts of colony life. In this study, we sought to determine whether stridulation can convey information in ant societies. We tested three main hypotheses using the Mediterranean ant Crematogaster scutellaris: (i) stridulation informs about the emitter’caste; (ii) workers can modulate stridulation based on specific needs, such as communicating the profitability of a food resource, or (iii) behavioural contexts. We recorded the stridulations of individuals from the three castes, restrained on a substrate, and the signals emitted by foragers workers feeding on honey drops of various sizes. Signals emitted by workers and sexuates were quantitatively and qualitatively distinct as was stridulation emitted by workers on different honey drops. Comparing across the experimental setups, we demonstrated that signals emitted in different contexts (restraining vs feeding) differed in emission patterns as well as certain parameters (dominant frequency, amplitude, duration of chirp). Our findings suggest that vibrational signaling represents a flexible communication channel paralleling the well-known chemical communication system.